فاعلية برنامج قائم على مداخل ما وراء المعرفة في تنمية مهارات القراءة التفسيرية للمفردات في النص القرآني للطلاب المعلمين شعبة اللغة العربية - عبده، أحمد عبده عوض; شهاب، صباح محمد أحمد; درويش، عفت حسن سعيد (جامعة كفر الشيخ - كلية التربية, 2021)
هدف هذا البحث إلى بناء برنامج قائم على مدخل ما وراء المعرفة، وقياس فاعليته في تنمية مهارات القراءة التفسيرية للمفردات في النص القرآني لدى الطلاب المعلمين شعبة اللغة العربية وتحددت مشكلة هذا البحث في ضعف مهارات القراءة التفسيرية للمفردات في النص القرآني لدى الطلاب المعلمين، وللوصول إلى حل هذه المشكلة سار البحث في مجموعة من الخطوات لعل من أهمها: - بناء قائمة بمهارات القراءة التفسيرية للمفردات، وتحديد أسس بناء برنامج قائم على مدخل ما وراء المعرفة، وتحديد خطوات بنائه المتمثلة في تحديد أهدافه، والمحتوي المراد تدريسه، وخطوات البرنامج، وإجراءاته، والأنشطة والوسائل المستخدمة، وتقويمه، وبناء دليل معلم لاستخدامه، وقياس فاعليته في تنمية مهارات القراءة التفسيرية للمفردات في النص القرآني لدى الطلاب المعلمين من خلال بناء اختبار وضبطه وتطبيق هذا الاختبار على مجموعة البحث قبليا، ثم تطبيق البرنامج على نفس المجموعة، ثم إعادة تطبيق هذا الاختبار على نفس المجموعة بعديا. وتوصل البحث إلى مجموعة من النتائج لعل من أهمها: -فاعلية البرنامج القائم على مدخل ما وراء المعرفة في تنمية مهارات القراءة التفسيرية للمفردات في النص القرآني للطلاب المعلمين شعبة اللغة العربية.
The aim of this research is to build a program based on a metacognitive approach, and to measure its effectiveness in developing the skills of interpretative reading of vocabulary in the Quranic text among teacher-students of the Arabic Language Department. Through this research, it has become clear that the problem is the weakness of explanatory vocabulary skills of Arabic Language Department. This problem went through a number of steps, perhaps the most important of them are: - Building a list of explanatory vocabulary reading skills. - Identifying the foundations for building a program based on a metacognitive approach, identifying the steps for building it represented in defining its objectives, the content to be taught, the program’s steps, procedures, activities and means used, in addition to evaluating this program. - Building a teacher’s guide for its use. - Measuring its effectiveness developing the interpretive reading skills of vocabulary in the Quranic text among teacher-students by constructing and controlling a test and applying this test to the research group first, then applying the program to the same group, and then re-applying this test to the same group later. The research reached a set of results, perhaps the most important of them is: The effectiveness of the program based on the approach to metacognition in developing the skills of interpretive reading of vocabulary in the Quranic text for teacher-students of the Arabic Language Department.
Keywords: البرامج التعليمية -- مدخل ما وراء المعرفة -- مهارات القراءة التفسيرية -- اللغة العربية -- طلبة الجامعات -- الوسائل التعليمية